An Overview of Current Progress and Challenges in Brain Cancer Therapy Using Advanced Nanoparticles - Chauhan, Mahima; Singh, Rahul P.; Sonali; Zia, Ghazala; Shekhar, Saurabh; Yadav, Bhavna; Garg, Vandana; Dutt, Rohit (Recent Patents on Nanotechnology, 2024)
Brain tumors pose significant challenges in terms of complete cure and early-stage prognosis. The complexity of brain tumors, including their location, infiltrative nature, and intricate tumor microenvironment (TME), contributes to the difficulties in achieving a complete cure. The primary objective of brain cancer therapy is to effectively treat brain tumors and improve the patient’s quality of life. Nanoparticles (NPs) have emerged as promising tools in this regard. They can be designed to deliver therapeutic drugs to the brain tumor site while also incorporating imaging agents. The NPs with the 10-200 nm range can cross the blood-brain barrier (BBB) and blood-brain tumor barrier (BBTB) and facilitate drug bioavailability. NPs can be designed by several methods to improve the pharmaceutical and pharmacological aspects of encapsulated therapeutic agents. NPs can be developed in various dosage forms to suit different administration routes in brain cancer therapy. The unique properties and versatility of NPs make them essential tools in the fight against brain tumors, offering new opportunities to improve patient outcomes and care. Having the ability to target brain tumors directly, overcome the BBB, and minimize systemic side effects makes NPs valuable tools in improving patient outcomes and care. The review highlights the challenges associated with brain tumor treatment and emphasizes the importance of early detection and diagnosis. The use of NPs for drug delivery and imaging in brain tumors is a promising approach to improving patient outcomes and quality of life. The versatility and unique properties of NPs make them valuable tools in the fight against brain tumors, and innovative NP-related patents have the potential to revolutionize healthcare.
Keywords: nanoparticles